2010
DOI: 10.1177/00333549101250s413
|View full text |Cite
|
Sign up to set email alerts
|

Economically Motivated Relationships and Transactional Sex among Unmarried African American and White Women: Results from a U.S. National Telephone Survey

Abstract: HIV/STI risk-reduction policies and programs in the U.S. need to explicitly address overall economic disempowerment among women, as well as racial disparities in poverty. These economic disparities likely contribute both to increasing rates of HIV among women in the U.S. and to the extraordinary racial disparities in HIV/STI risk among American women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 45 publications
6
81
1
Order By: Relevance
“…In a recent national study of trends of sexually transmitted diseases, 7% of African American women reported having been treated for an STI in the past year, although 16.6% of women in our study reported an STI in the past year (Chandra, Billioux, & Copen, 2012). Another study noted that 13.1% of African American women in the United States reported having engaged in transactional sex (Dunkle, Wingood, Camp, & DiClemente, 2010); however, 21.2% of our study population reported engaging in transactional sex in the past year.…”
Section: Resultscontrasting
confidence: 70%
“…In a recent national study of trends of sexually transmitted diseases, 7% of African American women reported having been treated for an STI in the past year, although 16.6% of women in our study reported an STI in the past year (Chandra, Billioux, & Copen, 2012). Another study noted that 13.1% of African American women in the United States reported having engaged in transactional sex (Dunkle, Wingood, Camp, & DiClemente, 2010); however, 21.2% of our study population reported engaging in transactional sex in the past year.…”
Section: Resultscontrasting
confidence: 70%
“…18,28 Often, circumstances of poverty and low education lead black women to be overly dependent on male partners, resulting in the use of sex as a survival mechanism. 29 In the case of female crack/ cocaine users and IDUs, sex in exchange for money or drugs is not uncommon. 18 Frequently, transactions of this nature neglect condom use primarily because of substance use intoxication 15,18 or lack of negotiating power on the part of the female user.…”
Section: Status and Support Losses In The Sexual Revolution: Diminishmentioning
confidence: 99%
“…Among adults, a recent study of adult African-American and white women found that 13% engaged in any exchange sex and 33% had maintained a sexual relationship for economic reasons. 11 Of the studies on the association between exchange sex and HIV infection in the United States, most have investigated drug users only. In 1994, Edlin et al 12 found nearly a 14-fold likelihood of sex exchange among women who had smoked crack, and Astemborski et al 13 observed a high prevalence of exchange sex among female injection drug users (IDUs).…”
Section: Introductionmentioning
confidence: 99%